Pertanggungjawaban Pidana Terhadap Pelaku Perbuatan Kekerasan Berbasis Gender Online Dengan Tipe Morphing - Syafirah Khansa Aribah Milansari (Jurist-Diction, 2024)
Abstract This study aims to look at the KBGO with the morphing type using a criminal law point of view and to see the criminal responsibility of the perpetrators of morphing. Currently, the regulations regarding KBGO, in this case, morphing, are still insufficient to enforce the law on the existence of online gender-based violence, online gender-based violence has the urgency to be discussed. At least. It can be seen that the main problem brought only to the occurrence of the criminal act of making, distributing, or providing pornography and the criminal act of manipulating Electronic Information or Electronic Documents with the aim that the Electronic Information or Electronic Documents are considered as if the data were authentic. In fact, in the realization of the crime, online gender-based violence has occurred, which in this paper has become a legal issue to be discussed.   Keywords: online gender-based violence, morphing, criminal liability.   Abstrak  Penelitian ini bertujuan untuk melihat KBGO dengan tipe morphing menggunakan sudut pandang hukum pidana dan melihat pertanggungjawaban pidana pelaku morphing. Saat ini peraturan mengenai KBGO, dalam hal ini morphing, masih belum cukup untuk melakukan penegakan hukum atas adanya perbuatan kekerasan berbasis gender online. Setidaknya. dapat dilihat bahwa persoalan utama yang dibawa hanya pada terjadinya tindak pidana membuat, menyebarluaskan, atau menyediakan pornografi dan tindak pidana melakukan manipulasi Informasi Elektronik dan/atau Dokumen Elektronik dengan tujuan agar Informasi Elektronik dan/atau Dokumen Elekronik tersebut dianggap seolah-olah data yang otentik.   Kata Kunci: Kekerasan berbasis gender online, morphing, pertanggungjawaban pidana.